2010
DOI: 10.1007/s00334-010-0258-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pollen spectra from modified Tauber traps and moss samples: examples from a selection of woodlands across Europe

Abstract: This paper compares pollen spectra derived from modified Tauber traps and moss samples from a selection of woodland types from Bulgaria, the Czech Republic, Georgia, Greece, Poland, Switzerland and Wales. The study examines the representation of individual taxa in the two sampling media and aims to ascertain the duration of pollen deposition captured by a moss. The latter aim was pursued through the calculation of dissimilarity indexes to assess how many years of pollen deposited in a pollen trap yield percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 32 publications
1
50
1
Order By: Relevance
“…The depositional environment has an influence on the pollen composition (Giesecke and Fontana 2008;Pardoe et al 2010) and when studying the pollen-vegetation relationship it is therefore important to standardize the size and type of sampling site as much as possible to reduce this variability. We aimed at sampling small lakes with a single, simple basin with as small a peat margin as possible and without permanent inflow.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…The depositional environment has an influence on the pollen composition (Giesecke and Fontana 2008;Pardoe et al 2010) and when studying the pollen-vegetation relationship it is therefore important to standardize the size and type of sampling site as much as possible to reduce this variability. We aimed at sampling small lakes with a single, simple basin with as small a peat margin as possible and without permanent inflow.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…However, he agreed with Caseldine (1981) who stated that the complete moss polster records at least 2 years of pollen rain. As other studies also showed that moss samples are likely to record one to five years of rain deposit (Räsänen et al, 2004;Pardoe et al, 2010), there is a general agreement to consider epigeic moss polsters as able to record at least one (often two) year of pollen production.…”
Section: Spatial and Temporal Scale Recorded By Mossmentioning
confidence: 80%
“…Since the maximum concentration of all identified biological objects in the ice core are within the period 1980-1990s, the calculation of average precipitation values for various types of ECM was performed for the period 1981-2000. A further justification for the use of this period only is that pollen productivity of individual plant species within the same plant communities can vary from year to year depending on the climatic conditions (Pardoe et al, 2010). However, pollen productivity for years within the dominant zonal circulation regime having similar climatic conditions (Bezuglova et.…”
Section: Resultsmentioning
confidence: 99%